2021
DOI: 10.1371/journal.pone.0251316
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported medication adherence among patients with diabetes or hypertension, Médecins Sans Frontières Shatila refugee camp, Beirut, Lebanon: A mixed-methods study

Abstract: Introduction Low adherence to medications, specifically in patients with Diabetes (DM) and Hypertension (HTN), and more so in refugee settings, remains a major challenge to achieving optimum clinical control in these patients. We aimed at determining the self-reported medication adherence prevalence and its predictors and exploring reasons for low adherence among these patients. Methods A mixed-methods study was conducted at Médecins Sans Frontières non-communicable diseases primary care center in the Shatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The predictive model had a moderate discriminative ability, which may be explained by missing predictors. 12,36,51,52 Furthermore, the calibration of the model showed overfitting, and the model may not perform well JAMA Network Open | Global Health in future samples; hence, future studies should aim to be larger if they wish to develop a predictive model. The study outcome was subjective and may be prone to misclassification; future studies should aim to measure blood pressure, cholesterol, and fasting glucose or hemoglobin A 1c and to collect symptoms and adherence using validated questionnaires.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The predictive model had a moderate discriminative ability, which may be explained by missing predictors. 12,36,51,52 Furthermore, the calibration of the model showed overfitting, and the model may not perform well JAMA Network Open | Global Health in future samples; hence, future studies should aim to be larger if they wish to develop a predictive model. The study outcome was subjective and may be prone to misclassification; future studies should aim to measure blood pressure, cholesterol, and fasting glucose or hemoglobin A 1c and to collect symptoms and adherence using validated questionnaires.…”
Section: Limitationsmentioning
confidence: 99%
“…A study conducted in 2018 on Palestinian refugees in Lebanon found that 30% of the sample had low adherence to medications. 12 Furthermore, refugee populations in Lebanon may have difficulty in adherence owing to poor access to health services, unavailability of medications, unaffordability of transportation, being food insecure, having limited health literacy, and other stressors. 13,14 In Lebanon, large populations of Syrian refugees are situated in the Bekaa valley and North Lebanon and reside in informal tented settlements or residential areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this study is one of the largest on older Syrian refugees in the published literature with a high response rate of >85% among those who were eligible. 11 The study was limited as the predictive model had a moderate discriminative ability, which may be explained by missing predictors, such as perception of medication regime as being complicated, not knowing the purpose of the medication, accessibility issues, side effects due to medication, lack of healthcare support, lack of trust in doctors, stressful living conditions and time since diagnosis 15,30,44,45 . Furthermore, the calibration of the model showed overfitting and may not perform well in future samples, hence, future studies should aim to be larger if they wish to develop a predictive model.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the management of NCDs among refugees in Lebanon and the Middle East, a region that hosts one of the largest refugee populations, are scarce. 15 Understanding the barriers and predictors of self-reported management of NCDs among older refugees, a population at high-risk, is important to allow resource allocation and contextualized humanitarian assistance to prevent premature mortality and morbidity. The present study aimed to elucidate the predictors of inability to manage NCDs in older Syrian refugees and describe barriers to accessing healthcare and managing these chronic conditions.…”
Section: Introductionmentioning
confidence: 99%